Consumption practices of thrifting: Cultural materialism analysis of consumer perspectives - Adiyani, Lady Khairunnisa; Khusyairi, Johny Alfian (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2025)
In the global era, people are looking for alternatives in fashion through the thrifting trend. This research aims to analyze the consumption practices of thrifting in Surabaya from a consumer perspective through Marvin Harris’ Cultural Materialism approach based on economic infrastructure, social structure, and cultural superstructure. This research uses a quantitative approach with descriptive methods. The data collection technique was a questionnaire with 110 respondents in Surabaya, with ages between 15-40 years. Based on the frequency and preference of thrift shopping, thrift consumption is influenced by affordable prices, ease of access, and the role of digital technology. Economic infrastructure, including thrift stores to online platforms, makes it easy for consumers to obtain high quality stuff at low prices. Based on cultural values and meanings, thrifting is a symbol of sustainability, creativity, and identity expression. The shift in cultural superstructure reflects that second-hand clothing is accepted as a fashionable alternative that reflects social responsibility and uniqueness. Based on economic relations and local culture, thrifting is an activity that increases the potential of the informal economy by creating business opportunities and strengthening social networks. This research concludes that thrifting is not only an economic alternative but also part of a lifestyle that refers to the value of sustainability and has an impact on local culture.